Changing trend in the seroprevalence and risk factors of human leptospirosis in the South Andaman Island, India. (6th June 2018) - Vimal Raj, Ratchagadasse; Vinod Kumar, Kirubakaran; Lall, Chandan; Vedhagiri, Kumaresan; Sugunan, Attayur Purushothaman; Sunish, Ittoop Pulikkottil; Sharma, Sameer; Vijayachari, Paluru
Abstract: Seroprevalence of leptospirosis among a healthy population of the South Andaman Island was assessed through random sampling. Previous studies have high seroprevalences of up to 55% in general population and 65% in agricultural labourers. The study subjects (1, 181 in total, 781 rural and 400 urban) were interviewed and tested for antibodies against Leptospira . Multivariate models were developed to determine the risk factors in the rural and the urban population. The overall seroprevalence was 10.9%, with rural (12.9%) being higher than the urban subjects (7.0%). The commonest infecting serogroup was Icterohaemorrhagiae (53.5%), followed by Grippotyphosa (13.2%). Compared to the earlier observation, seroprevalence was lower and an apparent shift in the infecting serogroup was found. This shift was in concordance with the changing trend in animal population. Significant difference in risk factors, both in rural and urban areas, was also observed. Similar trends in seroprevalence are being observed around the world. Therefore, time to time prevalence studies are needed for the development of effective control measure.